2020
DOI: 10.1016/j.ekir.2019.10.012
|View full text |Cite
|
Sign up to set email alerts
|

Secondary IgA Nephropathy Shares the Same Immune Features With Primary IgA Nephropathy

Abstract: Introduction: Galactose-deficient IgA1 (Gd-IgA1) and related IgA/IgG immune complexes have been identified as the key drivers in the pathogenesis of IgA nephropathy (IgAN). However, their roles in the development of secondary IgAN are still unknown. Methods: In this study, we measured the plasma Gd-IgA1 level, IgA/IgG complex, and Gd-IgA1 glomerular deposits in 100 patients with various kinds of secondary IgAN. Plasma Gd-IgA1 was measured using a lectin-based enzyme-linked immunosorbent assay, and Gd-IgA1 in g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
34
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 34 publications
(37 citation statements)
references
References 35 publications
2
34
0
Order By: Relevance
“…[ 13 ] Furthermore, Wang et al recently reported that secondary IgAN shared similar Gd-IgA1 with primary IgAN. [ 14 ] We believe the Gd-IgA1 was triggered by infection, since the secondary IgAN observed (IgA of lupus nephritis, hepatic IgAN, and Gd-IgA1) did not merge. [ 9 ] Additionally, as observed in our case, the Gd-IgA1 of staphylococcus associated glomerulonephritis showed weak to strong positive results.…”
Section: Discussionmentioning
confidence: 99%
“…[ 13 ] Furthermore, Wang et al recently reported that secondary IgAN shared similar Gd-IgA1 with primary IgAN. [ 14 ] We believe the Gd-IgA1 was triggered by infection, since the secondary IgAN observed (IgA of lupus nephritis, hepatic IgAN, and Gd-IgA1) did not merge. [ 9 ] Additionally, as observed in our case, the Gd-IgA1 of staphylococcus associated glomerulonephritis showed weak to strong positive results.…”
Section: Discussionmentioning
confidence: 99%
“…Gd-IgA1 is reported to increase in blood circulation and/or be deposited in renal mesangium in patients with primary IgAN and/or HSPN [ 25 28 ]. The data are sparse and controversial on whether immunostaining of KM-55, a Gd-IgA1-specific monoclonal antibody, is specific for patients with primary IgAN and HSPN, but not secondary form [ 6 , 7 , 29 ]. Here, we demonstrate glomerular KM55 staining with a similar pattern and intensity to IgA in this malignancy-associated HSPN, a secondary form of IgA deposition.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, in recent years, some experts have held the view that GALT might also be an important site for the production of Gd-IgA1, affecting the development of IgAN. Furthermore, it was evidenced that Gd-IgA1 was also present in patients with ulcerative colitis 59 . However, these findings were confined to sporadic cases and hence needed verification in large cohorts.…”
Section: The Mucosal Origin Of Gd-iga1mentioning
confidence: 99%